A corrosion-resistant coating on the surface of an impeller

The bonding layer was prepared by reacting modified aluminum oxide with epoxy phenolic resin, and a nickel-based tungsten carbide ceramic coating was installed on its surface, which solved the problem of poor wetting between the metal matrix and the ceramic reinforced phase, significantly improving the The bonding strength and thermal shock resistance of the coating enhance the wear and corrosion resistance of the overall material.

CN118685110BActive Publication Date: 2025-02-14INNER MONGOLIA BREGTON PUMP CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410876515.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-02
Publication Date
2025-02-14
Estimated Expiration
2044-07-02

AI Technical Summary

Technical Problem

The wetting properties between the existing metal matrix and the ceramic reinforced phase are poor, resulting in holes between the coating and the substrate, and the interface bonding is not ideal, which affects wear resistance and corrosion resistance.

Method used

Using a modifier as a functional additive, a phenolic resin with epoxy groups is prepared by reacting modified aluminum trioxide with epoxy phenolic resin, which is used to prepare a bonding layer and nickel-based carbonization is provided on the surface of the bonding layer. Tungsten ceramic coating improves the bonding strength and thermal shock resistance of the coating through vacuum cladding.

Benefits of technology

It significantly improves the bonding strength and thermal shock resistance between the ceramic coating and the metal matrix, reduces the interface slip between the coating and the matrix, enhances the plasticity and interface bonding strength of the overall material, and effectively improves the wear resistance and resistance. Corrosive.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a corrosion-resistant coating on the surface of an impeller, and relates to the technical field of coating materials. The invention discloses a corrosion-resistant coating on the surface of an impeller, comprising a bonding layer coated on the surface of the impeller, and a nickel-based tungsten carbide ceramic coating arranged on the surface of the bonding layer; the bonding layer is obtained by mixing a modifier, triolein, anhydrous ethanol, glycerol, di-n-octyl phthalate, and cyclohexanone and then brushing the mixture on the surface of a metal substrate; the application prepares a bonding layer between the ceramic coating and the metal substrate, which not only improves the bonding strength between the ceramic coating and the metal substrate, but also effectively eliminates the thermal stress generated by the mismatch of the expansion coefficient between the metal substrate and the ceramic coating, thereby achieving a toughening effect and improving the thermal shock resistance and life of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coating materials, and in particular to a corrosion-resistant coating on the surface of an impeller. Background Art

[0002] In the field of oil field production, water injection pump is an important equipment for oil field oil production and water injection. Water is injected into the target layer through the rotation of the impeller and guide wheel of the water injection pump. As the base material of the flow-through parts of the water pump, metal castings have the characteristics of high mechanical strength and strong machinability. However, when the centrifugal water injection pump is in operation, due to the action of centrifugal force, a low-pressure area less than the saturation pressure corresponding to the liquid temperature will be formed at the acute angle of the water pump impeller, etc., where the liquid will be gasified and the dissolved gas will overflow to form small bubbles. The bubbles flow from the low-pressure area to the high-pressure area with the fluid. The pressure change causes the bubbles to burst, forming a local vacuum area. The vacuum area forms a local high-frequency water hammer, which continuously acts on the surface of the metal casting, causing the metal casting surface to fatigue and damage; on the other hand, the active gas in the escaped gas condenses and releases heat, which chemically corrodes the surface of the metal casting, causing honeycomb or sponge-like corrosion pits to appear on the surface of the metal casting. Due to the complex quality of injected water, the corrosion and wear of the impeller and guide vane in the pump flow section is accelerated, the wear causes the pump efficiency to decrease, and the reinjected water corrodes the water injection equipment. The existing water injection pumps in service generally have the problem of low pump efficiency. Therefore, improving the wear resistance and corrosion resistance of pump parts has become the primary way to solve the problem.

[0003] Composite a layer of metal-based tungsten carbide ceramic coating on the surface of metal castings, which can greatly improve the wear resistance and cavitation resistance of water pump flow parts, and effectively extend the service life of equipment. However, the performance of composite materials is greatly affected by the interface bonding condition, which mainly depends on the chemical bonding and lattice matching between the metal matrix and the ceramic reinforcement phase. The better the chemical bonding and lattice matching, the lower the interface energy and the better the wettability. Under the condition of no brittle interface phase, the better the mechanical properties of composite materials. However, the wettability between the vast majority of ceramic reinforcement phases and liquid metal is poor, and casting penetration must be performed under pressure. Despite this, there are still certain holes between the processed coating and the matrix, and the interface bonding is still not ideal. Summary of the invention

[0004] The purpose of the present invention is to provide a corrosion-resistant coating on the surface of an impeller guide wheel to solve the following technical problems:

[0005] The existing metal matrix and ceramic reinforcement phase have poor wettability. Despite casting infiltration under pressure, there are still certain holes between the processed coating and the matrix, and the interface bonding is still not ideal.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A corrosion-resistant coating on the surface of an impeller, the corrosion-resistant coating comprising a bonding layer coated on the surface of the impeller, and a nickel-based tungsten carbide ceramic coating arranged on the surface of the bonding layer;

[0008] The preparation method of the bonding layer comprises the following steps: blending a modifier, triolein, anhydrous ethanol, glycerol, di-n-octyl phthalate and cyclohexanone to obtain a slurry; brushing the slurry on a pretreated substrate, drying naturally, repeating the brushing and drying steps, brushing the slurry on the surface of the pretreated substrate 3-5 times, and obtaining an impeller with a bonding layer on the surface;

[0009] The preparation method of the modifier comprises the following steps:

[0010] S1: Add nano-aluminum oxide, toluene and triethylamine into a reaction bottle and disperse them evenly, add γ-aminopropyltriethoxysilane, control the temperature at 100-110°C, keep the temperature under reflux for 1-3 hours, filter, wash and dry to obtain amino-modified aluminum oxide;

[0011] S2: In a nitrogen atmosphere, amino-modified aluminum oxide and tetrahydrofuran are added to reactor A, dipentyl iron formaldehyde and anhydrous ethanol are mixed and added to reactor A, the temperature is controlled to reflux for 3-6 hours, naturally cooled to room temperature, reacted at room temperature for 6-9 hours, anhydrous ethanol is added, allowed to stand, filtered and dried to obtain modified aluminum oxide;

[0012] S3: Add epoxy phenolic resin, xylene and modified alumina into reactor B, control the temperature to 50-60°C, keep the temperature for 3-6 hours under stirring, and perform reduced pressure distillation to obtain a modifier.

[0013] As a further embodiment of the present invention, the slurry comprises the following raw materials in weight percentage: 45-55% modifier, 0.004-0.01% triolein, 40-45% anhydrous ethanol, 0.4-0.8% propylene glycol, 0.4-0.8% di-n-octyl phthalate, and 2-5% cyclohexanone, and the sum of the weight percentages of the raw materials is 100%.

[0014] As a further solution of the present invention: the addition ratio of nano-aluminum oxide, toluene, triethylamine, and γ-aminopropyltriethoxysilane in S1 is 10g: 200-400mL: 0.3-0.6g: 10-15g.

[0015] As a further solution of the present invention: the addition ratio of amino-modified aluminum oxide, tetrahydrofuran, dipentyl iron formaldehyde, and anhydrous ethanol in S2 is 10g: 100-400mL: 5-10g: 100-200mL.

[0016] As a further solution of the present invention: the addition ratio of epoxy phenolic resin, xylene and modified alumina in S3 is 10g:100-150mL:2-3g.

[0017] As a further embodiment of the present invention: the preparation method of epoxy phenolic resin comprises the following steps:

[0018] A1: Phenol, formaldehyde solution and oxalic acid are added to a reaction kettle, heated to reflux for 0.5-1h, heating is stopped, hydrochloric acid is added to adjust the pH to 1-2, the temperature is adjusted to 90-95°C, the reaction is carried out until the reaction liquid becomes milky white and opaque, the temperature is kept for 30-45min, heating is stopped, the pH is adjusted to neutral, and vacuum dehydration is carried out to obtain a phenolic resin;

[0019] A2: In a nitrogen atmosphere, add epichlorohydrin, phenolic resin and tetrabutylammonium bromide into a reaction kettle and disperse them evenly. Control the temperature at 90-100°C and keep the temperature for reaction for 1-3 hours. Control the temperature at 75-85°C, add sodium hydroxide solution and keep the temperature for reaction for 3-6 hours. Distill under reduced pressure and extract with methanol to obtain epoxy phenolic resin.

[0020] As a further solution of the present invention: the formaldehyde solution in A1 is a 37 wt % formaldehyde aqueous solution; the addition ratio of phenol, formaldehyde solution and oxalic acid is 100:70-100:0.4-0.8.

[0021] As a further solution of the present invention: the sodium hydroxide solution in A2 is a 40-50wt% sodium hydroxide aqueous solution; the addition ratio of epichlorohydrin, phenolic resin, tetrabutylammonium bromide and sodium hydroxide solution is 40-65g:10g:0.2-0.4g:4-6g.

[0022] As a further solution of the present invention: the preparation method of the nickel-based tungsten carbide ceramic coating includes the following steps: mixing a binder, a self-fluxing alloy powder, and a nickel-coated tungsten carbide powder to obtain a slurry, placing the slurry on the surface of an impeller with a bonding layer for vacuum cladding to obtain a nickel-based tungsten carbide ceramic coating.

[0023] As a further solution of the present invention: the self-fluxing alloy powder includes the following components in mass percentage: 3.1%-3.5% B, 0.8%-0.95% C, 15%-17% Cr, 9.6%-9.9% Fe, 4%-4.5% Si, and the balance is Ni. The particle size of the self-fluxing alloy powder is 30-45um; the nickel-coated tungsten carbide powder includes the following components in mass percentage: 10%-30% Ni, 70%-90% WC, and the particle size of the nickel-coated tungsten carbide powder is 45-75um.

[0024] As a further solution of the present invention: the nickel-based tungsten carbide ceramic coating contains 15-30wt% WC.

[0025] As a further solution of the present invention: the binder is obtained by mixing rosin and anhydrous ethanol in a volume ratio of 1:4; the binder accounts for 3-6% of the total mass of the slurry.

[0026] As a further scheme of the present invention: the specific steps of vacuum cladding are: placing in a drying box at a working temperature of 80-120°C and pre-baking for 1-3h; then placing in a vacuum furnace with a vacuum degree of 10-50Pa, controlling the heating rate to 3-5°C / min, heating to 550-600°C, controlling the heating rate to 6-10°C / min, heating to 1140-1170°C, keeping warm for 3-10min, cooling with the furnace to 150-180°C, and air cooling to room temperature after taking out of the furnace.

[0027] As a further solution of the present invention: the preparation method of the pre-treated substrate includes the following steps: removing the oxide on the surface of the metal substrate with a grinding wheel, then washing with alcohol and acetone in sequence, and drying. The purpose is to make the surface of the substrate flat, free of defects such as oil stains, oxide films, pores and impurity particles, and avoid smoke or light absorption during processing that affects the cladding effect.

[0028] As a further solution of the present invention: the nickel-based tungsten carbide ceramic coating has a thickness of 0.5-1 mm.

[0029] As a further solution of the present invention: the thickness of the bonding layer is 0.2-0.5 mm.

[0030] Beneficial effects of the present invention:

[0031] (1) In the present application, phenol and formaldehyde are first reacted under the action of an acidic catalyst, oxalic acid, to obtain a linear phenolic resin, and then reacted with excess epichlorohydrin in the presence of sodium hydroxide to obtain an epoxy phenolic resin; the bonding strength between the phenolic resin and the metal substrate is effectively improved, and the thermal stability is also greatly improved. Based on nano-alumina, the present application first uses an aminosilane coupling agent to organically treat the nano-alumina to obtain amino-modified alumina; then the aldehyde group of formaldehyde dipentyl iron reacts with the amino group on the surface of the amino-modified alumina to obtain a modified alumina grafted with iron; finally, the amino group on the surface of the modified alumina reacts with the epoxy group of the epoxy phenolic resin to obtain a modifier. The present application uses a modifier as a functional auxiliary agent, triolein as a dispersant, anhydrous ethanol as a solvent, propylene glycol and di-n-octyl phthalate as plasticizers, and cyclohexanone as a homogenizer to prepare a slurry, and the slurry is coated on the surface of a metal substrate to prepare a bonding layer.

[0032] The slurry used in the present application for preparing the bonding layer contains a phenolic resin with epoxy groups, iron elements grafted on the phenolic resin, aluminum oxide and silicon-containing molecular chains, and a good interface diffusion resistance is formed between the bonding layer and the metal substrate. The aluminum oxide layer formed after the bonding layer is sintered at a high temperature gives the substrate good antioxidant properties. The iron elements evenly dispersed in the bonding layer are transferred and dispersed through the interface to reduce the degradation of the performance of the substrate and the bonding layer during service; as the heating temperature increases and the insulation time increases, the fluidity of the ceramic coating increases, the ceramic coating flows and fills the pores in the bonding layer, and the bonding strength of the ceramic coating is increased.

[0033] The bonding layer prepared in the present application is arranged between the metal substrate and the ceramic coating, which not only improves the physical compatibility between the ceramic and the metal and plays a role in high-temperature oxidation resistance, but also improves the problem of the difference in expansion coefficients between the ceramic coating and the metal substrate material, reduces the thermal stress caused by the difference in thermal expansion coefficients between the ceramic layer and the metal substrate, enhances the bonding ability between the ceramic and the metal substrate, and improves the bonding strength and thermal shock resistance of the coating. The bonding layer set in the present application also alleviates the problem of interface slip caused by direct bonding between the ceramic layer and the substrate, giving the material as a whole good plasticity and interface bonding strength.

[0034] (2) In the process of preparing nickel-based tungsten carbide ceramic coating by vacuum cladding method, under a certain vacuum degree, the vacuum furnace is first controlled to heat up slowly to slowly discharge impurities such as moisture and grease in the coating; then the vacuum furnace is controlled to heat up quickly to reach the target temperature of the molten material, and the alloy material adhering to the surface of the substrate is radiated with sufficient heat energy, melts in a short time and infiltrates the entire surface of the substrate, and the alloy material and the substrate form a mutual dissolution phenomenon on the interface under the action of the bonding layer, expand each other and react chemically, and form a mutual melting zone between the cladding layer and the substrate. As the temperature decreases, the coating and the mutual melting zone recrystallize, and the coating and the substrate form a metallurgical bonding zone with high bonding strength and dense structure. The metallurgical bonding at the junction of the cladding layer and the substrate is good, and defects such as pores and cracks rarely occur. In the present application, a Ni-based metal ceramic coating with micro-nano WC particles as the reinforcing phase is prepared on the surface of a metal substrate with a bonding layer by vacuum cladding technology. The composite coating prepared by the present application has the characteristics of being firm, dense and wear-resistant, effectively reducing the wear of the substrate and increasing the service life of the substrate. DETAILED DESCRIPTION

[0035] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1

[0036] The preparation method of epoxy phenolic resin comprises the following steps:

[0037] A1: 100 g of phenol, 70 g of 37 wt% formaldehyde aqueous solution, and 0.5 g of oxalic acid were added to a reaction kettle, heated to reflux for 0.5 h, the heating was stopped, hydrochloric acid was added to adjust the pH to 1, the temperature was adjusted to 90° C., the reaction was continued until the reaction solution became milky white and opaque, the temperature was kept warm for 45 min, the heating was stopped, the pH was adjusted to neutral, and vacuum dehydration was performed to obtain a phenolic resin;

[0038] A2: In a nitrogen atmosphere, 65 g of epichlorohydrin, 10 g of phenolic resin, and 0.2 g of tetrabutylammonium bromide were added to a reactor and dispersed evenly. The temperature was controlled at 95°C and the reaction was kept warm for 2 h. The temperature was controlled at 85°C, 6 g of 42 wt% aqueous sodium hydroxide solution was added, and the reaction was kept warm for 6 h. The epoxy phenolic resin was obtained by vacuum distillation and extraction with methanol. Example 2

[0039] The preparation method of the modifier comprises the following steps:

[0040] S1: Add 10g of nano-aluminum oxide, 200mL of toluene, and 0.3g of triethylamine into a reaction bottle and disperse them evenly, add 10g of γ-aminopropyltriethoxysilane, control the temperature to 100°C, keep the temperature under reflux for 1h, filter, wash, and dry to obtain amino-modified aluminum oxide;

[0041] S2: In a nitrogen atmosphere, 10 g of amino-modified aluminum oxide and 100 mL of tetrahydrofuran were added to reactor A, 5 g of dipentyl iron formaldehyde and 100 mL of anhydrous ethanol were mixed and added to reactor A, the temperature was controlled to reflux for 3 h, naturally cooled to room temperature, reacted at room temperature for 6 h, anhydrous ethanol was added, and the mixture was allowed to stand for suction filtration and dried to obtain modified aluminum oxide;

[0042] S3: Add 10 g of the epoxy phenolic resin prepared in Example 1, 100 mL of xylene and 2 g of modified alumina into reactor B, control the temperature to 50° C., keep warm for 3 h under stirring, and perform reduced pressure distillation to obtain a modifier. Example 3

[0043] The preparation method of the modifier comprises the following steps:

[0044] S1: Add 10g of nano-aluminum oxide, 300mL of toluene, and 0.5g of triethylamine into a reaction bottle and disperse them evenly, add 12g of γ-aminopropyltriethoxysilane, control the temperature to 110°C, keep the temperature under reflux for 1h, filter, wash, and dry to obtain amino-modified aluminum oxide;

[0045] S2: In a nitrogen atmosphere, 10 g of amino-modified aluminum oxide and 300 mL of tetrahydrofuran were added to reactor A, 7 g of dipentyl iron formaldehyde and 150 mL of anhydrous ethanol were mixed and added to reactor A, the temperature was controlled to reflux for 4 h, naturally cooled to room temperature, reacted at room temperature for 8 h, anhydrous ethanol was added, and the mixture was allowed to stand for suction filtration and dried to obtain modified aluminum oxide;

[0046] S3: Add 10 g of the epoxy phenolic resin prepared in Example 1, 120 mL of xylene, and 2.5 g of modified alumina into reactor B, control the temperature to 55° C., keep warm for 4 h under stirring, and perform reduced pressure distillation to obtain a modifier. Example 4

[0047] The preparation method of the modifier comprises the following steps:

[0048] S1: Add 10g of nano-aluminum oxide, 400mL of toluene, and 0.6g of triethylamine into a reaction bottle and disperse them evenly, add 15g of γ-aminopropyltriethoxysilane, control the temperature to 110°C, keep the temperature under reflux for 3h, filter, wash, and dry to obtain amino-modified aluminum oxide;

[0049] S2: In a nitrogen atmosphere, 10 g of amino-modified aluminum oxide and 400 mL of tetrahydrofuran were added to reactor A, 10 g of dipentyl iron formaldehyde and 200 mL of anhydrous ethanol were mixed and added to reactor A, the temperature was controlled to reflux for 6 h, naturally cooled to room temperature, reacted at room temperature for 9 h, anhydrous ethanol was added, and the mixture was allowed to stand for suction filtration and dried to obtain modified aluminum oxide;

[0050] S3: Add 10 g of the epoxy phenolic resin prepared in Example 1, 150 mL of xylene, and 3 g of modified alumina into reactor B, control the temperature to 60° C., keep warm for 6 h under stirring, and perform reduced pressure distillation to obtain a modifier. Example 5

[0051] A method for preparing a corrosion-resistant coating on the surface of an impeller guide wheel comprises the following steps:

[0052] A1: Preparation of pre-treated substrate: using a grinding wheel to remove oxides on the surface of the metal substrate, then cleaning with alcohol and acetone in sequence, and drying to obtain a pre-treated substrate;

[0053] A2: 55 g of the modifier prepared in Example 2, 0.01 g of triolein, 42 g of anhydrous ethanol, 0.05 g of propylene glycol, 0.05 g of di-n-octyl phthalate, and 2.89 g of cyclohexanone were mixed to obtain a slurry; the pretreated substrate was coated with the slurry, dried naturally, and the coating and drying steps were repeated to coat the surface of the pretreated substrate with the slurry to obtain an impeller having a bonding layer with a thickness of 0.5 mm on the surface;

[0054] A3: The self-fluxing alloy powder includes the following components in mass percentage: 3.11% B, 0.82% C, 16.5% Cr, 9.7% Fe, 4.1% Si, and the balance is Ni. The particle size of the self-fluxing alloy powder is 30-45um; the nickel-coated tungsten carbide powder includes the following components in mass percentage: 10% Ni, 90% WC, and the particle size of the nickel-coated tungsten carbide powder is 45-75um; the rosin and anhydrous ethanol are mixed in a volume ratio of 1:4 to obtain the binder;

[0055] A4: A slurry is obtained by mixing a binder, a self-fluxing alloy powder, and a nickel-coated tungsten carbide powder, wherein the binder accounts for 6% of the total mass of the slurry; the slurry is placed on the surface of the impeller with a bonding layer prepared in Example 1, and placed in a drying oven at an operating temperature of 80°C and pre-baked for 2 hours; then placed in a vacuum furnace with a vacuum degree of 10Pa, and the heating rate is controlled to be 3°C / min, and the temperature is raised to 600°C, and the heating rate is controlled to be 10°C / min, and the temperature is raised to 1150°C and kept warm for 6 minutes, and then cooled to 180°C with the furnace, and then air-cooled to room temperature after being taken out of the furnace to obtain a nickel-based tungsten carbide ceramic coating with a thickness of 0.8 mm; the nickel-based tungsten carbide ceramic coating contains 25wt% WC. Example 6

[0056] Compared with Example 5, Example 6 is only replaced by the modifier prepared in Example 2 used in Example 5 with the modifier prepared in Example 3, and the other components and preparation methods are completely the same as those in Example 5. Example 7

[0057] Compared with Example 5, Example 7 is that only the modifier prepared in Example 2 used in Example 5 is replaced by the modifier prepared in Example 4, and the other components and preparation method are exactly the same as those in Example 5.

[0058] Comparative Example 1

[0059] The preparation method of phenolic resin comprises the following steps: adding 100g of phenol, 70g of 37wt% formaldehyde aqueous solution and 0.5g of oxalic acid into a reaction kettle, heating and reflux for 0.5h, stopping heating, adding hydrochloric acid to adjust the pH to 1, adjusting the temperature to 90°C, reacting until the reaction liquid becomes milky white and opaque, continuing to keep warm for 45min, stopping heating, adjusting the pH to neutral, vacuum dehydrating, and obtaining phenolic resin.

[0060] Comparative Example 2

[0061] The preparation method of the modifier comprises the following steps:

[0062] S1: Add 10g of nano-aluminum oxide, 300mL of toluene, and 0.5g of triethylamine into a reaction bottle and disperse them evenly, add 12g of γ-aminopropyltriethoxysilane, control the temperature to 110°C, keep the temperature under reflux for 1h, filter, wash, and dry to obtain amino-modified aluminum oxide;

[0063] S2: In a nitrogen atmosphere, 10 g of amino-modified aluminum oxide and 300 mL of tetrahydrofuran were added to reactor A, 7 g of dipentyl iron formaldehyde and 150 mL of anhydrous ethanol were mixed and added to reactor A, the temperature was controlled to reflux for 4 h, naturally cooled to room temperature, reacted at room temperature for 8 h, anhydrous ethanol was added, and the mixture was allowed to stand for suction filtration and dried to obtain modified aluminum oxide;

[0064] S3: Add 10 g of the phenolic resin prepared in Comparative Example 1, 120 mL of xylene, and 2.5 g of modified alumina into reactor B, control the temperature to 55° C., keep warm for 4 h under stirring, and perform reduced pressure distillation to obtain a modifier.

[0065] Comparative Example 3

[0066] The preparation method of the modifier comprises the following steps:

[0067] S1: Add 10g of nano-aluminum oxide, 300mL of toluene, and 0.5g of triethylamine into a reaction bottle and disperse them evenly, add 12g of γ-aminopropyltriethoxysilane, control the temperature to 110°C, keep the temperature under reflux for 1h, filter, wash, and dry to obtain amino-modified aluminum oxide;

[0068] S2: 10 g of amino-modified aluminum oxide and 7 g of dipentyl iron formaldehyde are mixed to obtain modified aluminum oxide;

[0069] S3: Add 10 g of the epoxy phenolic resin prepared in Example 1, 120 mL of xylene, and 2.5 g of modified alumina into reactor B, control the temperature to 55° C., keep warm for 4 h under stirring, and perform reduced pressure distillation to obtain a modifier.

[0070] Comparative Example 4

[0071] The preparation method of the modifier comprises the following steps:

[0072] S1: Add 10g of nano-aluminum oxide, 300mL of toluene, and 0.5g of triethylamine into a reaction bottle and disperse them evenly, add 12g of γ-aminopropyltriethoxysilane, control the temperature to 110°C, keep the temperature under reflux for 1h, filter, wash, and dry to obtain amino-modified aluminum oxide;

[0073] S2: Add 10 g of the epoxy phenolic resin prepared in Example 1, 120 mL of xylene, and 2.5 g of modified alumina into reactor B, control the temperature to 55° C., keep warm for 4 h under stirring, and perform reduced pressure distillation to obtain a modifier.

[0074] Comparative Example 5

[0075] A method for preparing a corrosion-resistant coating on the surface of an impeller guide wheel comprises the following steps:

[0076] A1: Preparation of pre-treated substrate: using a grinding wheel to remove oxides on the surface of the metal substrate, then cleaning with alcohol and acetone in sequence, and drying to obtain a pre-treated substrate;

[0077] A2: The self-fluxing alloy powder includes the following components in mass percentage: 3.11% B, 0.82% C, 16.5% Cr, 9.7% Fe, 4.1% Si, and the balance is Ni. The particle size of the self-fluxing alloy powder is 30-45um; the nickel-coated tungsten carbide powder includes the following components in mass percentage: 10% Ni, 90% WC, and the particle size of the nickel-coated tungsten carbide powder is 45-75um; the rosin and anhydrous ethanol are mixed in a volume ratio of 1:4 to obtain a binder;

[0078] A3: A binder, a self-fluxing alloy powder, and a nickel-coated tungsten carbide powder are mixed to obtain a slurry, in which the binder accounts for 6% of the total mass of the slurry; the slurry is placed on the surface of the impeller with a bonding layer prepared in Example 1, and placed in a drying oven at a working temperature of 80°C and pre-baked for 2 hours; then placed in a vacuum furnace with a vacuum degree of 10Pa, and the heating rate is controlled to be 3°C / min, and the temperature is increased to 600°C, and the heating rate is controlled to be 10°C / min, and the temperature is increased to 1150°C and kept warm for 6 minutes, and then cooled to 180°C with the furnace, and then air-cooled to room temperature after being taken out of the furnace to obtain a nickel-based tungsten carbide ceramic coating with a thickness of 0.8 mm; the nickel-based tungsten carbide ceramic coating contains 25wt% WC.

[0079] Comparative Example 6

[0080] Compared with Example 5, Comparative Example 6 is the case in which only the modifier prepared in Example 2 used in Example 5 is replaced by the modifier prepared in Comparative Example 2, and the remaining components and preparation method are completely consistent with those of Example 5.

[0081] Comparative Example 7

[0082] Compared with Example 5, Comparative Example 7 is that only the modifier prepared in Example 2 used in Example 5 is replaced by the modifier prepared in Comparative Example 3, and the remaining components and preparation method are completely consistent with Example 5.

[0083] Comparative Example 8

[0084] Compared with Example 5, Comparative Example 8 is that only the modifier prepared in Example 2 used in Example 5 is replaced by the modifier prepared in Comparative Example 4, and the other components and preparation method are completely consistent with Example 5.

[0085] Performance Testing

[0086] (1) Tensile bond strength: According to the test method of GB / T 8642-2002 "Determination of tensile bond strength of thermal spraying", the test results are shown in Table 1;

[0087] (2) Microhardness: According to the determination method of GB / T 4340.1-2009 "Vickers hardness test for metallic materials. Part 1: Test method", MVD-1000JMT2 computer digital display micro Vickers hardness tester was used, the substrate was 45# steel, the load was 0.98N, and the holding time was 10s. The test results are shown in Table 1;

[0088] (3) Anti-cavitation performance: According to GB / T 6383-2009 "Vibration Cavitation Test Method", the test results are shown in Table 1;

[0089] Table 1: Statistical table of performance test data of Examples 5-7 and Comparative Examples 5-8

[0090]

[0091] As can be seen from Table 1, the coating prepared in the present application has excellent tensile bonding strength with the metal casting, and has the characteristics of high microhardness and excellent cavitation resistance.

[0092] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A corrosion-resistant coating on the surface of an impeller, characterized in that: The corrosion-resistant coating comprises a bonding layer coated on the surface of the impeller, and a nickel-based tungsten carbide ceramic coating arranged on the surface of the bonding layer; The preparation method of the bonding layer comprises the following steps: blending a modifier, triolein, anhydrous ethanol, glycerol, di-n-octyl phthalate, and cyclohexanone to obtain a slurry; brushing the slurry on a pretreated substrate, drying naturally, repeating the brushing and drying steps, brushing the slurry on the surface of the pretreated substrate 3-5 times, and obtaining an impeller with a bonding layer on the surface; The preparation method of the modifier comprises the following steps: S1: Add nano-aluminum oxide, toluene and triethylamine into a reaction bottle and disperse them evenly, add γ-aminopropyltriethoxysilane, control the temperature at 100-110°C, keep the temperature under reflux for 1-3 hours, filter, wash and dry to obtain amino-modified aluminum oxide; S2: In a nitrogen atmosphere, amino-modified aluminum oxide and tetrahydrofuran are added to reactor A, dipentyl iron formaldehyde and anhydrous ethanol are mixed and added to reactor A, the temperature is controlled to reflux for 3-6 hours, naturally cooled to room temperature, reacted at room temperature for 6-9 hours, anhydrous ethanol is added, allowed to stand, filtered and dried to obtain modified aluminum oxide; S3: Add epoxy phenolic resin, xylene and modified alumina into reactor B, control the temperature to 50-60°C, keep the temperature for 3-6 hours under stirring, and perform reduced pressure distillation to obtain a modifier.

2. The corrosion-resistant coating on the surface of an impeller according to claim 1, characterized in that: The slurry comprises the following raw materials in weight percentage: 45-55% modifier, 0.004-0.01% triolein, 40-45% anhydrous ethanol, 0.4-0.8% propylene glycol, 0.4-0.8% di-n-octyl phthalate, and 2-5% cyclohexanone, and the sum of the weight percentages of the raw materials is 100%.

3. The corrosion-resistant coating on the surface of an impeller according to claim 1, characterized in that: The addition ratio of nano-aluminum oxide, toluene, triethylamine, and γ-aminopropyltriethoxysilane in S1 is 10g: 200-400mL: 0.3-0.6g: 10-15g.

4. The corrosion-resistant coating on the surface of an impeller according to claim 1, characterized in that: The addition ratio of amino-modified aluminum oxide, tetrahydrofuran, dipentyl iron formaldehyde, and anhydrous ethanol in S2 is 10g:100-400mL:5-10g:100-200mL.

5. The corrosion-resistant coating on the surface of an impeller according to claim 1, characterized in that: The addition ratio of epoxy phenolic resin, xylene and modified alumina in S3 is 10g:100-150mL:2-3g.

6. The corrosion-resistant coating on the surface of an impeller according to claim 1, characterized in that: The preparation method of the nickel-based tungsten carbide ceramic coating comprises the following steps: a binder, a self-fluxing alloy powder and a nickel-coated tungsten carbide powder are mixed to obtain a slurry, and the slurry is placed on the surface of an impeller with a bonding layer for vacuum cladding to obtain a nickel-based tungsten carbide ceramic coating.

7. The corrosion-resistant coating on the surface of the impeller according to claim 6 is characterized in that: The self-fluxing alloy powder includes the following components in mass percentage: 3.1%-3.5% B, 0.8%-0.95% C, 15%-17% Cr, 9.6%-9.9% Fe, 4%-4.5% Si, and the balance is Ni. The particle size of the self-fluxing alloy powder is 30-45um; the nickel-coated tungsten carbide powder includes the following components in mass percentage: 10%-30% Ni, 70%-90% WC, and the particle size of the nickel-coated tungsten carbide powder is 45-75um.

8. The corrosion-resistant coating on the surface of an impeller according to claim 6, characterized in that: The nickel-based tungsten carbide ceramic coating contains 15-30wt% WC.

9. The corrosion-resistant coating on the surface of an impeller according to claim 6, characterized in that: The binder is obtained by mixing rosin and anhydrous ethanol in a volume ratio of 1:4; the binder accounts for 3-6% of the total mass of the slurry.

10. The corrosion-resistant coating on the surface of an impeller according to claim 6, characterized in that: The specific steps of the vacuum cladding are: placing in a drying box at a working temperature of 80-120°C and pre-baking for 1-3h; then placing in a vacuum furnace with a vacuum degree of 10-50Pa, controlling the heating rate to 3-5°C / min, heating to 550-600°C, controlling the heating rate to 6-10°C / min, heating to 1140-1170°C, keeping warm for 3-10min, cooling with the furnace to 150-180°C, and air cooling to room temperature after taking out of the furnace.

Citation Information

Patent Citations

  • High-toughness and abrasion-proof laser cladding nickel-base alloy powder and preparation method thereof

    CN102943199A

  • Corrosion resistant ceramic paint and preparation method thereof

    CN104403381A